ต้นทุนการผลิตน้ำนมของฟาร์มโคนมขนาดเล็กและขนาดกลางของสหกรณ์โคนมป่าตึงห้วยหม้อ จำกัด จังหวัดเชียงใหม่และจังหวัดลำพูน - คณกร พินิจศร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Milk production cost has been increased, causing dairy farmers got less net profit. Factors of milk production cost had been studied. Data of milk production cost were collected from 50 (direct-personal) farmers’ interview in 12 months consecutively. Data analyses with Logistic Regression and Student’s T-test were performed. The results demonstrated that the average milk production cost was 14.72±2.78 Baht/kg (Small farm’s milk production cost was 15.66±2.99 Baht/kg and Medium farm’s milk production cost was 13.27±1.56 Baht/kg) under the study period. Cost of milk production included variable cost 82.47±2.49% (50.37% was feed cost), fixed cost 16.98±0.78% and opportunity cost 0.55%. Farms with more milk production (in 305 days) and less calving interval had significantly lower in milk production cost. In addition, farms size, frequency to feed concentrate, body condition score, criterion to confirm adequacy of roughage intake, rumen acidosis, knowledge and time to first service knowledge were associated with milk production cost (p<0.05). Nevertheless, somatic cell counts, different cows’ proportion and total solids had no significant difference concerning milk production cost in this study (p>0.05).